2015
DOI: 10.1017/s0033583515000074
|View full text |Cite
|
Sign up to set email alerts
|

Chiral discrimination in NMR spectroscopy

Abstract: Abstract. Nuclear magnetic resonance is the most important form of molecular spectroscopy in chemistry and biochemistry but it is normally blind to chirality. It was predicted in 2004 that precessing nuclear spins in chiral molecules in a liquid in a strong magnetic field induce a rotating electric polarization that is of opposite sign for enantiomers. This polarization arises from the distortion of the electronic structure by the nuclear magnetic moment in the presence of the strong magnetic field and is equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Lately, the influence of magnetic fields on the properties of chiral molecules has been a subject of great interest. Recently, the influence of magnetic field on the mobility of chirally polarized mixtures of 1-phenylethanol was studied using proton nuclear magnetic resonance ( 1 H NMR) . It was shown that the diffusion coefficients in the pure form and in the chirally polarized mixture of 1-phenylethanol molecules tend to be equalized when the magnetic field is increased.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, the influence of magnetic fields on the properties of chiral molecules has been a subject of great interest. Recently, the influence of magnetic field on the mobility of chirally polarized mixtures of 1-phenylethanol was studied using proton nuclear magnetic resonance ( 1 H NMR) . It was shown that the diffusion coefficients in the pure form and in the chirally polarized mixture of 1-phenylethanol molecules tend to be equalized when the magnetic field is increased.…”
Section: Introductionmentioning
confidence: 99%
“…From Eqs. ( 14), (18) and (19), we conclude that . Experimentally, the enantiodiscrimination exactly disappears when the DP of L-and D-polypeptide are as close as possible [135].…”
Section: Achiral Oriented Systems By Compensationmentioning
confidence: 60%
“…Methods based on Nuclear Magnetic Resonance (NMR) spectroscopy [8] have also been explored for the determination of enantiomeric purity, since this technique provides unique insights into the atomiclevel structure and dynamics of gases, liquids and solids [8,9,10,11,12,13,14,15]. In a strong magnetic field, precessing nuclear spins in chiral molecules in an isotropic liquid induce a rotating electric polarization of opposite signs for enantiomers [16,17,18]. Alternatively, an applied electric field should also induce distinct NMR signals for enantiomers in an isotropic liquid [19].…”
Section: General Introductionmentioning
confidence: 99%
“…Buckingham [333,334] emphasized that additional terms are to be added to the expression for the electric polarization, equations (111) and (112), to account for the contribution of the magnetic shielding tensor of nucleus J to the mean component of the permanent molecular electric dipole µ (0) , i.e.…”
Section: Contribution Of Molecular Electric Dipole and Antisymmetric ...mentioning
confidence: 99%